"Let him speak:" a descriptive qualitative study of the roles and behaviors of family companions in primary care visits among older adults with cognitive impairment. (6th June 2017) - Vick, Judith B.; Amjad, Halima; Smith, Katherine C.; Boyd, Cynthia M.; Gitlin, Laura N.; Roth, David L.; Roter, Debra L.; Wolff, Jennifer L.
Abstract : Objective: Cognitive impairment poses communication challenges in primary care. Although family "companions" commonly attend primary care visits of older adults with cognitive impairment, little is known about how their involvement affects communication. Therefore, we sought to understand how companion involvement affects the quality of primary care visit communication for older adults with cognitive impairment. Methods: Cross‐sectional, descriptive qualitative study participants were as follows: (1) English‐speaking adults age 65 or older with mild, moderate, or severe cognitive impairment; (2) family members or other unpaid companions who accompany older adults to primary care visits; and (3) primary care clinicians. Twenty semi‐structured and in‐depth qualitative interviews of older adults and their companions ( N = 20 dyads) and two focus groups ( N = 10 primary care clinicians) were conducted. Interviews and focus groups were transcribed and analyzed thematically. Results: Family companions commonly facilitate communication by advocating for patients, ensuring the accuracy of information exchange and understanding, and preserving rapport. Significant communication challenges were also identified, including patient and companion role ambiguity, competing visit agendas, and primary care clinician confusion regarding the most accurate source of information. Patients, companions, and clinicians each identified strategies to improve communication, chief among them being to identify, differentiate, and respect both patient and companion priorities and perspectives. Conclusions: Family companions actively participate in primary care visits of older adults with cognitive impairment in ways that promote and inhibit effective communication. Findings suggest the need for strategies that more effectively and purposefully involve family in the care of primary care patients with cognitive impairment. Copyright © 2017 John Wiley & Sons, Ltd.